Formulation and Antibacterial Activity Test of Hand Soap Gel from Ethanol Extract of Bay Leaf (Syzygium nervosum DC) - Noni Rahayu Putri; Epi Supri Wardi; Arnela Sukma Ningsih; Miftahur Rahmi (UIN Sulthan Thaha Saifuddin Jambi, 2025)
Background: Bay leaf (Syzygium nervosum DC) is one of the plants that has antibacterial activity that can be used as an active substance in hand soap gel preparations of bay leaf ethanol extract. To formulate a hand soap gel preparation from ethanol extract of bay leaf and evaluate its antibacterial activity. This study is experimental in nature. The research includes the preparation of a concentrated extract from bay leaves and its characterization, followed by the formulation of hand soap gel from the ethanol extract of bay leaves in four different concentrations: F1: 7.5%, F2: 10%, and F3: 12.5%. Evaluation of the physical quality of the formulations includes organoleptic properties, homogeneity, pH testing, viscosity testing, and stability testing. The antibacterial activity of the hand soap gel formulation is assessed using the replica method. The physical evaluation results of the hand soap gel meet the SNI standards. The average percentage decrease in the number of colonies was as follows F0 = 31.8%, F1 = 59.4%, F2 = 81.1%, F3 = 83.2% and the comparison preparation (brand B*) was 83.3%. Bay leaf ethanol extract hand soap gel is capable of inhibiting bacterial growth using the replica method.